Downstream metabolites of (+)-cis-12-oxo-phytodienoic acid function as noncanonical bioactive jasmonates in Arabidopsis thaliana - Minoru Ueda; Rina Saito; Yuho Nishizato; Tsumugi Kitajima; Nobuki Kato (Nature Communications)
Abstract (+)-cis-12-oxo-phytodienoic acid (cis-OPDA) is a biosynthetic precursor of the plant hormone (+)−7-iso-Jasmonoyl-L-isoleucine (JA-Ile). It was proposed as an endogenous chemical signal independent of the JA-Ile receptor COI1-JAZ in Arabidopsis thaliana. The bioactive form of cis-OPDA that induces COI1-JAZ-independent gene expression remains unknown. Here we demonstrate that the downstream metabolites of cis-OPDA, especially tetranor-cis-OPDA (tn-cis-OPDA) and 7-iso-4,5-didehydro-JA (4,5-ddh-JA), upregulate the expression of the OPDA marker genes such as ZAT10 and ERF5. These downstream metabolites function independently of the JA-Ile-COI1-JAZ-MYCs canonical jasmonate signaling module, and their electrophilic α, β-unsaturated carbonyl functionalities are essential for their bioactivity. These results raise a possibility that the downstream metabolites of cis-OPDA would function as endogenous chemical signal in A. thaliana.